The system of long-term care in Poland - Stanislawa Golinowska (Center for Social and Economic Research (CASE), 2010)
In the field of social protection, Poland belongs to the EU group of countries with the familybased welfare model, what is extremely visible for the long-term care where family is the main care provider for elderly individuals with limitations in activities of daily living. At the same time the proportion of elderly in the coming decades is projected to be among the highest in the European Union, what raises questions on the design of the long-term care. For the moment the system is highly unregulated and disintegrated between social assistance and health care services. But it is the health sector that concentrates policy debate with a proposal of an introduction of nursing insurance. In the social sector, the significant changes that were favorable to LTC services development were introduced by the law on the social assistance (2004) and family benefits (2003) widening the scope of care available at home and in adult day care centers. But still provision of services is insufficient and a market of private services, paid out-of-pocket rapidly develops. It seems that main problems of the long-term care development in the future will be raising demand against insufficient resources and diversified priorities of the health care system.
Keywords: H51; H55; I18; 330; long-term care; health care system; social assistance; elderly; Poland; Langzeitpflege; Sozialer Dienst; Öffentliche Sozialleistungen; Gesundheitswesen; Sozialpolitik; Polen